The contribution of science learning to the formation of positive emotions in early childhood - Nafiqoh, Heni; Dwi Nurcahyani, Ratna; Suryamah, Suryamah; Khotimah, Fanny (IKIP Siliwangi, 2025)
Science learning has a very important role in early childhood development, because it can help them explore the contribution of science to the formation of positive emotions. This can be seen from the emotions of children in group A at KB Lab PAUD Terpadu Tunas Siliwangi, who have not been able to express their emotions naturally. Therefore, this study aims to develop positive emotions in children through the application of science learning. The method used in this research is descriptive qualitative, which includes direct observation and interviews. The research was conducted for eight meetings, involving eight children as subjects, consisting of four boys and four girls. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. At the initial meeting, it was seen that the children began to show emotional development. However, after eight meetings, the results showed that science learning significantly increased children's curiosity, excitement and satisfaction. This contributed positively to their emotional development, creating a more supportive learning environment.